The Impact of Vocational Education on Youth Employment in South Sulawesi - Sukniati, Sukniati; Tasik, Yunita; Reski, Nur Fitrah (Educia Journal, 2023)
This research aims at analyzing the effects of vocational training on young employee in the South Sulawesi province concerning curriculum comprehensiveness, teachers’ performance, economic constraints and interaction with organizations. This study employs a qualitative cross sectional survey in which a group of students, employers and educators were interviewed to get an understanding of the efficiency of the vocational training and its impact on employment opportunities. The study evidences a clear disconnect in the vocational curricula to meet the market and career requirements; the existing courses neglect to prepare the students for many skills and competencies that are expected of them in the job market. Similarly, socio economic barriers including financial difficulties as well as the fact that some students have to work in order to take care of their families were revealed to be significant barriers to vocational education. The study also acknowledges extensive cooperation with the industries and undertaking of apprentice programs to improve on the practical skills and employability. Solutions include modifications in curricula to reflect the current market demand, the incorporation of soft skills and computer literacy as whistle Gowons, extending the network of company relations, and the change of policies that hinder the learners’ chances and boost the development of the region. It is important to note that these findings will enhance the understanding of vocational education in the context of the study area that is South Sulawesi and could be relevant for enhancing the quality of vocational education and employment chances.